THE EFFECT OF ENVIRONMENTAL MANAGEMENT ACCOUNTING (EMA) AND GREEN TRANSFORMATIONAL LEADERSHIP (GTL) ON ENVIRONMENT, SOCIAL, AND GOVERNANCE (ESG) PERFORMANCE : INTERNAL AND EXTERNAL SOCIAL CAPITAL AS MODERATING - Vierina Clyde; Intan Puspanita; Asih Machfudzoh; Kurniarga Bagaskara; Selly Anggraeni Haryono (Pascasarjana Universitas Sultan Ageng Tirtayas, 2026)
This study aims to examine the effect of Environmental Management Accounting (EMA) and Green Transformational Leadership (GTL) on Environmental, Social, and Governance (ESG) Performance, with Internal Social Capital and External Social Capital as moderating variables. The research adopts a quantitative approach using hypothesis testing and Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze the relationships among variables. The population of this study consists of 311 managers working in manufacturing companies in the Greater Jakarta area (JABODETABEK), Indonesia.The results indicate that Environmental Management Accounting (EMA) has a positive and significant effect on ESG Performance, suggesting that better implementation of environmental accounting practices enhances organizations’ sustainability outcomes. Green Transformational Leadership (GTL) is also found to have a positive influence on ESG Performance, indicating that leaders who promote environmental values and sustainability-oriented behavior contribute to improving organizational ESG outcomes.Furthermore, Internal Social Capital is found to have a limited moderating role in strengthening the relationship between EMA, GTL, and ESG Performance. Similarly, External Social Capital also shows a weak moderating effect in enhancing the relationship between EMA, GTL, and ESG Performance. These findings suggest that while social capital contributes to organizational sustainability, its moderating influence in this context remains limited.This study highlights the importance of Environmental Management Accounting and Green Transformational Leadership in improving ESG Performance. The findings also provide insights that strengthening internal and external organizational relationships alone may not be sufficient to significantly enhance sustainability performance without strong environmental management systems and effective leadership support. This study contributes to the growing literature on sustainability accounting, leadership, and ESG performance, particularly in the context of manufacturing companies in Indonesia.